Incremental exercise test for the evaluation of peak oxygen consumption in paralympic swimmers - de Souza, H.; Da Silva Alves, E.; Ortega, L.; Silva, A.; Esteves, A. M.; Schwingel, P. A.; Vital, R.; Da Rocha, E. A.; Rodrigues, B.; Lira, F. S.; Tufik, S.; De Mello, M. T. (The Journal of Sports Medicine and Physical Fitness, 2016)
BACKGROUND: Peak oxygen consumption (VO2peak) is a fundamental parameter used to evaluate physical capacity. The objective of this study was to explore two types of incremental exercise tests used to determine VO2peak in four Paralympic swimmers: arm ergometer testing in the laboratory and testing in the swimming pool.